2007
DOI: 10.17221/692-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Dry heat inactivation of Bacillus cereus in rice

Abstract: Houška M., Kýhos K., Landfeld A., Průchová J., Schlemmerová L., Šmuhařová H., Špelina V., Novotná P. (2007): Dry heat inactivation of Bacillus cereus in rice. Czech J. Food Sci., 25: 208-213.The aim of this work was to validate the method of decontamination of rice at the temperature of 120°C (determined as optimal in previous experiments). Bacillus cereus was selected as the marker micro-organism for the monitoring of decontamination. The spores of Bacillus cereus are moderately heat resistant. In order to sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 6 publications
0
9
0
1
Order By: Relevance
“…For instance, B. cereus spores can survive temperature as high as 95°C for 2 min or 85°C for 32 min (Byrne et al, ). However, Houska et al () found that treatment at 120°C for 1 hr can significantly inactivate heat resistant bacterial spores.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, B. cereus spores can survive temperature as high as 95°C for 2 min or 85°C for 32 min (Byrne et al, ). However, Houska et al () found that treatment at 120°C for 1 hr can significantly inactivate heat resistant bacterial spores.…”
Section: Resultsmentioning
confidence: 99%
“…This my duo to the fact that the cooking process may effect on the count of aerobic spore forming bacteria, its ability to form active spore or toxins. (Parry and Gilbert, 1980), (Houška et al, 2007) and (Desai and Varadaraj, 2010).…”
Section: Results Inmentioning
confidence: 99%
“…Generally, this involves either a moderate heat treatment (<75 °C) designed to kill pathogenic vegetative cells, termed pasteurization, or a higher heat treatment (>5 min at 121 °C at the coldest spot), termed sterilization, canning, or retorting, to enhance the shelf‐life and safety of the food items, and this includes the inactivation of spores of Bacillus and Clostridium species (Oomes and others ). A dry heat operation in which rice was heated to 120°C in a sterilizer for 1 h has been validated as a method of inactivating B. cereus spores (Houska and others ). In thermal processing, the term D ‐value is used to define the time required at any specific temperature to inactivate 90% of the bacterial population of concern.…”
Section: Bacillus Sporesmentioning
confidence: 99%